Bonn Climate Talks 2013 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
On 4 June, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) convened a side event on Agriculture and Mitigation: Towards Low Emissions Development. The side event was well-attended and sparked interesting discussions on new tools and methods for low emissions development linked to agriculture.